Public awareness of tick-borne diseases - Czerwińska Pawluk, Iwona; Stój-Kontraktowicz, Monika; Zukow, Walery (Journal of Education, Health and Sport, 2024)
Background: Tick-borne diseases, due to their all too frequent occurrence, the different localisation of organ lesions and the numerous complications in their course, are a serious medical problem. The public’s knowledge of the biological hazards posed by ticks and the possibilities for their prevention is the basis for taking important measures to minimise the risk of tick-borne infections. Aim of the study: To assess the public’s knowledge of tick-borne diseases. Material and methods: The study was carried out among 137 people living in the villages of Studzianki Pancerne and Kozienice in the Kozienice district. The method used in the study was a diagnostic survey, the technique was a questionnaire, and the research tool was an original survey questionnaire developed for the purposes of the study. Results: Respondents’ knowledge of tick-borne diseases is unsatisfactory. Only 11.7% of the total number of respondents had a high level of knowledge in this area. 53.3% had a low level of knowledge and 35<0% had a medium level of knowledge. The study confirmed a statistically significant relationship between the level of knowledge of the subjects and age (p=0.001), past tick bite episode (p=0.001), past disease or treatment (p=0.001). No significant correlations were found between respondents’ knowledge and gender (p=0.951), education (p=0.062) and place of residence (p= 0.717). Conclusions: The level of knowledge of respondents about tick-borne diseases is insufficient. The results indicate the need for large-scale educational activities, which should be extended to different age groups, regardless of their place of residence and level of education.